2019
DOI: 10.3748/wjg.v25.i33.4933
|View full text |Cite
|
Sign up to set email alerts
|

Proton pump inhibitor use increases mortality and hepatic decompensation in liver cirrhosis

Abstract: BACKGROUNDProton pump inhibitors (PPIs) are widely prescribed, often without clear indications. There are conflicting data on its association with mortality risk and hepatic decompensation in cirrhotic patients. Furthermore, PPI users and PPI exposure in some studies have been poorly defined with many confounding factors.AIMTo examine if PPI use increases mortality and hepatic decompensation and the impact of cumulative PPI dose exposure.METHODSData from patients with decompensated liver cirrhosis were extract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 35 publications
0
34
0
1
Order By: Relevance
“…Among the 12 patients in the PH group, 11 were taking proton pump inhibitors (PPIs), so the relationship between the ongoing use of PPIs for the treatment of varices was also taken into consideration (12)(13)(14)(15). It has been reported that the partial changes in the gut microbiota caused by PPI usage are similar to the changes caused by the progression of liver cirrhosis, and increased inflow of oral flora to the intestines might create an intestinal environment that is a risk factor for the progression of liver cirrhosis, spontaneous bacterial peritonitis, and hepatic encephalopathy (9,(16)(17)(18)(19). The levels of genera (Lactobacillales, Streptococcus, Selenomonas, Veillonella, Campylobacter, and Haemophilus) have been reported to be high in PPI users (20).…”
Section: Discussionmentioning
confidence: 99%
“…Among the 12 patients in the PH group, 11 were taking proton pump inhibitors (PPIs), so the relationship between the ongoing use of PPIs for the treatment of varices was also taken into consideration (12)(13)(14)(15). It has been reported that the partial changes in the gut microbiota caused by PPI usage are similar to the changes caused by the progression of liver cirrhosis, and increased inflow of oral flora to the intestines might create an intestinal environment that is a risk factor for the progression of liver cirrhosis, spontaneous bacterial peritonitis, and hepatic encephalopathy (9,(16)(17)(18)(19). The levels of genera (Lactobacillales, Streptococcus, Selenomonas, Veillonella, Campylobacter, and Haemophilus) have been reported to be high in PPI users (20).…”
Section: Discussionmentioning
confidence: 99%
“…An early meta-analysis published in 2015 showed that PPI use was not associated with increased mortality in patients with cirrhosis [11]. However, only four cohort studies [14,16,17,19] were included in the present study, and many related cohort studies have been published since the previous meta-analysis [18,[20][21][22][23][24][25][26][27][28][29][30][31][32][33][34]. In addition, it remains unknown…”
Section: Introductionmentioning
confidence: 89%
“…Overall, 21 cohort studies with 20,899 patients and 7457 death events were included, of which 16 were retrospective cohort studies [16][17][18][19][22][23][24][25][26][27][28][29][30][31][32][33], while the other five were prospective cohort [14,15,20,21,34]. As for the ethnicity of the patients, 12 studies included Caucasian patients [15,16,18,[20][21][22]24,28,29,[32][33][34], 7 included Asians [17,19,23,25,26,30,31], and the remaining 2 included patients with mixed ethnicity [14,27]. Most of the studies included patients with hospitalized patients with cirrhosis without serious clinical complications [14][15][16][17][18]…”
Section: Study Characteristics and Quality Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…(73) Greater PPI exposure has also been reported to increase the risk of liver-related hospitalization and mortality. (74,75) In critically ill patients with decompensated cirrhosis admitted to a medical ICU, NSAIDs were associated with 46.1% of the instances of preventable medication-related harm, including melena or hematemesis and worsening renal function (reduced creatinine clearance). (14) Other studies demonstrated a decreased glomerular filtration rate by ~30% in patients with compensated cirrhosis, (42,43) explained by the inhibition of prostaglandin synthesis, which decreases vasodilation of the afferent renal arterioles.…”
Section: Medication Pkpd Change Clinical Impact Remarksmentioning
confidence: 99%